2021
DOI: 10.1007/s13311-020-00974-8
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic Facilitation of Forelimb Functional Recovery in Rats with Cervical Spinal Cord Injury

Abstract: Serotonergic agents can improve the recovery of motor ability after a spinal cord injury. Herein, we compare the effects of buspirone, a 5-HT 1A receptor partial agonist, to fluoxetine, a selective serotonin reuptake inhibitor, on forelimb motor function recovery after a C4 bilateral dorsal funiculi crush in adult female rats. After injury, single pellet reaching performance and forelimb muscle activity decreased in all rats. From 1 to 6 weeks after injury, rats were tested on these tasks with and without busp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 67 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…28 In a previous study, we showed that an incremental dose of Buspirone (1 to 2 mg/kg) can improve forelimb reaching function in rats with cervical cord injury. 29 The spontaneous recovery of forelimb function of rats without any drug intervention was found to be less than 20% while the rats which were administered Buspirone reached a success rate of over 60% by 6 weeks post-injury. Thus, serotonergic modulation enabled over 3-fold improvements in forelimb reaching and grasping after post-injury Buspirone administration.…”
Section: Discussionmentioning
confidence: 95%
“…28 In a previous study, we showed that an incremental dose of Buspirone (1 to 2 mg/kg) can improve forelimb reaching function in rats with cervical cord injury. 29 The spontaneous recovery of forelimb function of rats without any drug intervention was found to be less than 20% while the rats which were administered Buspirone reached a success rate of over 60% by 6 weeks post-injury. Thus, serotonergic modulation enabled over 3-fold improvements in forelimb reaching and grasping after post-injury Buspirone administration.…”
Section: Discussionmentioning
confidence: 95%
“…Serotonergic agonists have been used extensively to promote motor recovery after SCI (35)(36)(37)(38)(39)(40)(41)(42)(43). However, only transient benefits were observed in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…While the longevity of motor gains is remarkable, serotonergic therapy was initiated the day after SCI. Furthermore, serotonergic interventions were delivered during the acute or subacute phase of the injury in all the above studies (35)(36)(37)(38)(39)(40)(41)(42)(43)79). However, the majority of SCI patients have chronic injuries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations